Contributions of Colonic Short-Chain Fatty Acid Receptors in Energy Homeostasis - Kuwahara, Atsukazu (Frontiers in Endocrinology, 2014)
The gastrointestinal (GI) tract is separated from the body’s internal environment by a single layer of epithelial cells, through which nutrients must pass for their absorption into the bloodstream. Besides food and drink, the GI lumen is also exposed to bioactive chemicals and bacterial products including short-chain fatty acids (SCFAs). Therefore, the GI tract has to monitor the composition of its contents continuously to discriminate between necessary and unnecessary compounds. Recent molecular identification of epithelial membrane receptor proteins has revealed the sensory roles of intestinal epithelial cells in the gut chemosensory system. Malfunctioning of these receptors may be responsible for a variety of metabolic dysfunctions associated with obesity and related disorders. Recent studies suggest that SCFAs produced by microbiota fermentation act as signaling molecules and influence the host’s metabolism; uncovering the sensory mechanisms of such bacterial metabolites would help us understand the interactions between the host and microbiota in host energy homeostasis. In this review, the contribution of colonic SCFA receptors in energy metabolism and our recent findings concerning the possible link between SCFA receptors and host energy homeostasis are discussed.